WAKAF TUNAI DAN PEMBERDAYAAN EKONOMI MASYARAKAT - Mashudi (LP2M IAIN Jember (now UIN Kiai Haji Achmad Siddiq Jember), 2016)
The management of endowment in Indonesia is less aimed at the economy empowerment of the people and tend to be just for the sake of worship. This ideology cannot be separated from the society’s understanding about the endowment. According to Indonesian people, endowment is a stationary object, such as land. Mustafa Edwin predicts about the potential of the endowment in Indonesia with the number of generous Muslims is estimated around 10 million with the average income of Rp 500.000 up to 10.000.000 monthly, so it can be accumulated around 3 trillion in every year from that endowmnet itself. If that data is managed productively, the sociey, especially poor people will be insatiable for their basic need.